Pengalaman berwirausaha jualan parfum velocity di kalangan mahasiswa - Subakir, Nizarudin Zahid (Maliki Interdisciplinary Journal, 2025)
Entrepreneurship activities among students serve as an effective practical learning tool for developing character, business skills, and an entrepreneurial mindset from an early age. This article explores students’ experiences in managing the Parfum Velocity perfume business, which began with market research to understand trends, consumer preferences, and analyze competitors as the foundation for marketing strategies. The promotional strategies employed include digital marketing through social media, word-of-mouth promotion, and participation in campus bazaars to expand reach and build direct relationships with consumers. Despite facing challenges such as intense competition, limited capital, time management, and logistics, the students were able to overcome these obstacles through creativity and effective management. As a result, they gained various important skills such as managerial, communication, and negotiation skills, as well as increased self-confidence and financial independence. This experience demonstrates that engaging in entrepreneurship not only enhances practical competencies but also prepares students for the workforce and creates opportunities for future business ventures.